2014
DOI: 10.1007/s40135-014-0047-3
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Keratitis: Update for 2014

Abstract: Fungal keratitis is a challenging problem worldwide, and many obstacles remain to the effective prevention, diagnosis, and therapy of this vision-threatening condition. Recent research has highlighted progress in each of these facets of the clinical approach to keratomycosis. Increased awareness of contact lens-associated fungal keratitis has prompted regulators to pay greater attention to testing of contact lens solutions under realworld conditions. Related research has also delved into the mechanisms of fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
5
0
1
Order By: Relevance
“…However, eyes have physical, chemical and enzymatic barriers to prevent the proliferation of pathogenic microorganisms. Fungi that caused keratitis exhibit virulence factors that allow them to colonise this organ 38 . Additionally, predisposing factors (eg corneal lesions, defects in the corneal epithelium or misuse of contact lenses) allow for the colonisation of pathogens 32,39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, eyes have physical, chemical and enzymatic barriers to prevent the proliferation of pathogenic microorganisms. Fungi that caused keratitis exhibit virulence factors that allow them to colonise this organ 38 . Additionally, predisposing factors (eg corneal lesions, defects in the corneal epithelium or misuse of contact lenses) allow for the colonisation of pathogens 32,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and early diagnosis of FK remains a challenge. 17 Given the fact that good clinical outcome of FK largely relies on timely and appropriate antifungal intervention upon early diagnosis, there is a need for novel diagnostic tools that are non-invasive, highly sensitive and specific for ocular fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The number of drug formulations is restricted; thus, therapeutic options are limited to a few and often expensive drug preparations. 15,16 A Cochrane systematic review demonstrated that there is no evidence about the efficacy of the current available topical preparations, most probably owing to the small sample size of existing studies. 17 Furthermore, the use of antimicrobial agents increases the appearance of reduced susceptibility, which in the worst cases can evolve in open resistance.…”
Section: Introductionmentioning
confidence: 99%